Bioaccumulation of heavy metals by the yeast S. cerevisiae and the bioremediation of industrial waste water - Stoll, Anita (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1997)
Water is an essential element in all aspects of life and is vital for both domestic and industrial purposes regarding both the quality and quantity thereof. Similar to many other drought stricken countries, South Africa requires water for the socio-economic growth of the country, yet is faced with the problem of maintaining the quality of its drinking water as well as protecting the dwindling supplies. In an attempt to prevent the deterioration of South African water supplies the treatment, purification and recycling of industrial and mining waste water has recently become of prime importance. Many industrial and mining waste waters contain heavy metals in toxic quantities. The conventional processes that have been used till recently to address this problem, are often expensive or contain chemical agents which compound the environmental problem. As an alternative biological methods of metal accumulation appear to offer an economic and efficient alternative to these methods. An advantage to the South African scenario is the commercial production of the yeast, S. cerevisiae as a readily inexpensive by-product from some fermentation industries, Yeast cells, and in particular S. cerevisiae have proven to be capable of accumulating heavy metals, and therefore exhibit potential application in the bioremediation of waste water. The aim of this project was twofold. The initial part of this work attempted to define the mechanisms of metal accumulation by the yeast cells and cellular components. The information obtained from these initial studies provided a data base required for the development of a bioremediation system. Initial contact with the metal ions occurs at the wall interface of the yeast cell. Metal accumulation appears to be a function of all the cell wall components. The isolated cell wall components are better metal chelators then the intact cell walls. An apparent affinity series of mannan > chitin> glucan > intact cell walls exists. However, these components differ in their affinities for metal ions. Storage of metal ions within the cell occurs predominantly in the vacuole. The present study concluded that metal accumulation by the vacuole could be related to size. Metal accumulation occurred in the order of Cu2+ > Co2+ > Cd2+ with a corresponding decrease in atomic radii of Cd2+ > C02+ > Cu2+. Vacuolar ion deposition occurs at an early stage during the internalization of metal ions within the yeast cells. At the onset of vacuolar saturation, depositions of metal ions as granules within the cytosol occurs. In the presence of heavy metal cations viable yeast cells can be shown to exhibit two types of cellular responses. Uptake of Cu2+ and Cd2+ causes the loss of intracellular physiological cations from within the yeast cell. In comparison, uptake of Co2+ into the cell does not have this effect. All three heavy metal cations initiate plasma cell membrane permeability, thus the Cu2+ and Cd2+ induced loss of the intracellular cations, occurs. ~ a result of ion-exchange mechanisms and not due to cation leakage brought about by membrane permeabilization. Uptake of heavy metals by viable yeasts appears to be generally non-selective though the amount of metals accumulated are largely affected by the ratio of ambient metal concentration to biomass quantity. In addition, the energy dependent nature of internalization necessitates the availability of an external energy source for metal uptake by viable yeast cells. For these reasons metal removal from industrial waste water was investigated using non-viable biomass. By immobilizing the yeast cells additional mechanical integrity and stability was conferred apon the biomass. The three types of biomass preparations developed in this study, viz. polyvinyl alcohol (PV A) Na-alginate, PV A Na-orthophosphate and alkali treated polyethylenimine (PEI):glutaraldehyde (GA) biomass pellets, all fulfilled the necessary physical requirements. However, the superior metal accumulating properties of the PEI:GA biomass determined its selection as a biosorbent for bioremediation purposes. Biosorption of heavy metals by PEI:GA biomass is of a competitive nature, with the amount of metal accumulated influenced by the availability of the metal ions. This availability is largely determined by the solution pH. At low pH values the affinity of the biomass for metals decreases, whilst enhanced metal biosorption occurs at higher pHs, ego pH 4.5 - 6.0. PEI:GA biomass pellets can be implemented -as a biosorbent for the bi9remediaiton of high concentration, low-volume metal containing industrial waste. Several options regarding the bioremediation system are available. Depending on the concentration of the metals in the effluent, the bioremediation process can either be used independently or as part of a biphasic remediation system for the treatment of waste water. Initial phase chemical modification may be required, whilst two types of biological systems can be implemented as 'part of the second phase. The PEI:GA biomass can either be contained within continuous-flow fixed bed tanks or continuous-flow stirred bioreactor tanks. Due to the simplicity of the process and the ease with which scale-up is facilitated, the second type of system shows greater application potential for the treatment of this type of industrial waste water than the fixed-bed systems.
Keywords: Saccharomyces cerevisiae; Yeast fungi -- Biotechnology; Metal ions; Bioremediation; Water -- Purification -- Biological treatment